APPLICATION OF SOLAR CELL SYSTEM FOR STREET LIGHTING AND INCREASING DIVERSIFICATION OF PROCESSED FISH FOR FISHERMEN AND HOUSEHOLD GROUPS TO INCREASE ECONOMIC RESILIENCE IN KELURAHAN LAMARU , KOTA BALIKPAPAN - Maria Ulfah; Andi Sri Irtawaty; Armin; Praseptia Gardiarini; Dessy Handa Sari (Jurnal Pengabdian Ahmad Yani, 2021)
The results of the survey and field observations to the Partner (Kelurahan Lamaru Balikpapan), the Balikpapan State Polytechnic Village Development team obtained information from interviews with the kelurahan that there were still RT-RT areas that lacked access to street lighting. Includes RT. 8, RT.19, RT 22, RT 23 RT 28. This lack of access to lighting results in frequent traffic accidents for motorists who cross the road and are not criminals at night or in dark conditions. In addition to the problems above, information was also obtained, that fish, which is one of the natural resources at partner locations, is still not optimally utilized because the average catch of residents is directly sold to traditional markets. as street lamp lighting in several RTs that have been determined above and Increasing Diversification of Processed Fish into Shredded and Nugget. The 5 lamp units that were installed were operating well and received a very positive appreciation by the residents. Residents are also given knowledge about solar cell technology and how to maintain the lamp unit so that its use can be maximized. The Village Development Team also conducted training on diversification of tongkol into shreds and nuggets to provide more value added which has an impact on improving the economy of residents at partner locations which is also accompanied by socialization related to the nutritional value of tongkol. In this Community Service Activity, this village development also carried out the handover of 5 units of village street lighting and a set of kitchen utensils for processing tongkol from the team to the kelurahan which was immediately received by the Lamaru village head.